APLIKASI PEMUPUKAN SUMBER P YANG BERBEDA TERHADAP PERTUMBUHAN DAN NODUL Pueraria javanica YANG DIINOKULASI DENGAN FUNGI MIKORIZA ARBUSKULAR DI ULTISOL - Simel Sowmen; Ifradi Ifradi; Arif Rachmat; Tri Silfani; Karyadinata Karyadinata (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2018)
This research was aims to assess effect of the different phospor fertilizer on the growth and nodules in Pueraria javanica inoculated with Arbuscular Fungi Micorrhyza. This experimental design was Completely Randomized Design (CRD) with three phospor fertilizer treatments: P0 = 0 kg/ha phosphor (0, g/pot), P1 = SP36 200 kg/ha (1 g/pot), and P2 = rock phosphate 200 kg/ha (1 g/pot), with four replicates. The whole pot treatments received mycorrhizal inoculation. The variables measured were plant height, number of leaves, number of branches, root length, number of root nodule, number of active nodules , and the percentage of active nodules. The results of data analysis show that the treatment has no effect (P > 0.05) for all parameters. The results showed that the presence of mycorrhizal inoculation, macro and micronutrient elements of Pueraria javanica already fulfilled without phosporus fertilizing in ultisol. Key words: AMF, phosphor, Root nodule, rock phosphate, Pueraria javanica